Design and optimization of integrated single mixed refrigerant processes for coproduction of LNG and high-purity ethane. (November 2020) - He, Ting; Lin, Wensheng
Abstract: In this study, two novel integrated single mixed refrigerant (SMR) processes are proposed to coproduce liquefied natural gas (LNG) and high-purity liquid ethane, which are suitable for improving the economic benefits of high ethane-containing natural gas. In Process 1, cryogenic distillation and conventional SMR process are integrated to separate ethane while producing LNG. Since the distillation pressure is below the critical pressure of methane, heat transfer temperature difference in the low temperature section may be relatively large. Therefore, in Process 2, the pressure of natural gas is increased by adding a compressor after the distillation column. Aspen HYSYS is used to simulate the proposed processes, and the key parameters of the refrigeration cycles are optimized by genetic algorithms. Based on the comprehensive consideration of initial investment and operating cost, Process 2 is recommended for large-scale plant, while Process 1 for small-scale plant and situations with requirement of simple system, for example floating LNG production (FLNG). Furthermore, a simplified Process 1, with propane eliminated from the mixed refrigerant, is presented for better adaption to FLNG conditions.